Choroidal hemangioma: MR findings and differentiation from uveal melanoma. - Stroszczynski, C; Hosten, N; Bornfeld, N; Wiegel, T; Schueler, A; Foerster, P; Lemke, A J; Hoffmann, K T; Felix, R (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE The aim of this study was to establish the MR imaging characteristics of choroidal hemangioma and to compare them with those of uveal melanoma.METHODS Among 41 patients examined at 1.5 T (4-cm surface coil, T1-weighted and fast spin-echo T2-weighted sequences), 25 had uveal melanoma and 16 had circumscribed choroidal hemangioma. After i.v. bolus injection of gadopentetate dimeglumine, dynamic and T1-weighted sequences were acquired.RESULTS In patients with choroidal hemangioma, uniform signal characteristics were detected on fast T2-weighted images. In 15 of 16 patients with choroidal hemangioma, lesions were isointense with vitreous on fast spin-echo T2-weighted images, whereas lesions in 24 of 25 patients with uveal melanoma were hypointense. Signal characteristics of uveal melanoma and hemangioma did not differ significantly on plain T1-weighted images. Enhancement was earlier and much stronger for circumscribed choroidal hemangioma than for uveal melanoma. After i.v. bolus application of gadopentetate dimeglumine, the increase of signal intensity was higher for circumscribed choroidal hemangioma (signal intensity ratio, 5.8) than for uveal melanoma (signal intensity ratio, 2.2).CONCLUSION Circumscribed choroidal hemangioma may be difficult to differentiate from melanoma by ophthalmologic examination. Differentiation may not be possible if direct viewing of uveal space-occupying lesions is hampered by opaque vitreous media. The characteristic findings on fast spin-echo T2-weighted MR images and early enhanced images aid in differentiating choroidal hemangioma from uveal melanoma.